Nomadic work in Costa Rica and the tourism panorama before it Covid-19, 2021 - Oviedo Vega, Adriana (2022)
The Pandemic brought with it a resounding falls for the tourism sector in Costa Rica, causing an economic and social collapse. However, a new form of work is emerging that will directly impact the country's tourism ecosystem: nomadic work. The objective of this research is to analyze the characteristics of this modality and if it will affect the resurgence of national tourism, since this style of work allows people from other countries to reside for a long stay in the country, either alone or with their families. Through an applied methodology that took into consideration bibliographic reviews, legislative documents, theoretical analyzes on the teleworking modality, consultation with experts and media monitoring analyzing variables such as: country, regulations, benefits, conditions for teleworking, among others. This research was substantiated. At the same time, Costa Rica made a political commitment to pass the "Law to attract remote workers and service providers of an international nature", increasing the chances that this modality will improve the national tourism landscape despite the Pandemic. However, an analysis is made of the digital gap that Costa Rica faces in light of this new labor alternative. It is possible to conclude from this research that nomadic work will have a direct impact on the increase in income of all the people involved with tourism in the country, especially those who reside in areas that offer more and better alternatives for connectivity, housing and infrastructure for this type of population.